LOCAL ANTI-INFLAMMATORY EFFECT OF GEL CONTAINING CONVOLVULUS ARVENSIS EXTRACT (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Many plants have been known to cure various diseases since ancient times. Even the oldest examples of writing, created in the years before Christ, contain information about the healing properties of plants. Some natural drugs considered valuable were isolated in pure form decades ago. But there are many plants that have not yet been studied and whose medicinal properties have not been scientifically tested.